Serpentinimonas gen. nov., Serpentinimonas raichei sp. nov., Serpentinimonas barnesii sp. nov. and Serpentinimonas maccroryi sp. nov., hyperalkaliphilic and facultative autotrophic bacteria isolated from terrestrial serpentinizing springs. Issue 8 (11th August 2021) - Bird, Lina J.; Kuenen, J. Gijs; Osburn, Magdalena R.; Tomioka, Naotaka; Ishii, Shun'ichi; Barr, Casey; Nealson, Kenneth H.; Suzuki, Shino
Abstract : Three highly alkaliphilic bacterial strains designated as A1 T, H1 T and B1 T were isolated from two highly alkaline springs at The Cedars, a terrestrial serpentinizing site. Cells from all strains were motile, Gram-negative and rod-shaped. Strains A1 T, H1 T and B1 T were mesophilic (optimum, 30 °C), highly alkaliphilic (optimum, pH 11) and facultatively autotrophic. Major cellular fatty acids were saturated and monounsaturated hexadecenoic and octadecanoic acids. The genome size of strains A1 T, H1 T and B1 T was 2 574 013, 2 475 906 and 2 623 236 bp, and the G+C content was 66.0, 66.2 and 66.1 mol%, respectively. Analysis of the 16S rRNA genes showed the highest similarity to the genera Malikia (95.1–96.4 %), Macromonas (93.0–93.6 %) and Hydrogenophaga (93.0–96.6 %) in the family Comamonadaceae . Phylogenetic analysis based on 16S rRNA gene and phylogenomic analysis based on core gene sequences revealed that the isolated strains diverged from the related species, forming a distinct branch. Average amino acid identity values of strains A1 T, H1 T and B1 T against the genomes of related members in this family were below 67 %, which is below the suggested threshold for genera boundaries. Average nucleotide identity by blast values and digital DNA–DNA hybridization among the three strains were below 92.0 and 46.6 % respectively, which are below the suggested thresholds for species boundaries. Based on phylogenetic, genomic and phenotypic characterization, we propose Serpentinimonas gen. nov., Serpentinimonas raichei sp. nov. (type strain A1 T =NBRC 111848 T =DSM 103917 T ), Serpentinimonas barnesii sp. nov. (type strain H1 T = NBRC 111849 T =DSM 103920 T ) and Serpentinimonas maccroryi sp. nov. (type strain B1 T =NBRC 111850 T =DSM 103919 T ) belonging to the family Comamonadaceae . We have designated Serpentinimonas raichei the type species for the genus because it is the dominant species in The Cedars springs.